2015
DOI: 10.1038/srep14983
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes and alternate promoter usage by human colon cancers for expressing DCLK1-isoforms: Clinical Implications

Abstract: DCLK1 specifically marks colon/pancreatic cancers in mice, and is expressed by human colon adenocarcinomas (hCRCs). Down-regulation of DCLK1 results in loss of cancer-stem-cells (CSCs), and inhibits spheroidal/xenograft growths from hCRC-cells. The 5′-promoter of DCLK1-gene is reportedly hypermethylated in hCRCs, resulting in loss of expression of DCLK1-transcripts, originating from 5′(α)-promoter (termed DCLK1-L, in here). However, in mouse colon-tumors, 5′-promoter of DCLK1-gene remains unchanged, and DCLK1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
167
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(190 citation statements)
references
References 57 publications
(140 reference statements)
10
167
0
1
Order By: Relevance
“…Thus, O'Connell and colleagues were able to reconcile the apparent contradictory findings of widespread epigenetic silencing of the Dclk1C gene on one hand, and the clear functional importance of the transcript in a broad variety of cancers on the other. 41 Accordingly, Dclk1 expression has been observed in neuroendocrine tumors of the mammary gland and the rectum, 42,43 consistent with the known expression of Dclk1 in neuronal and enteroendocrine cells, but no specific role for Dclk1 in these tumors has been suggested so far. Finally, the relevance of Dclk1 expression in esophageal cancer is presently unclear, 44 but the cells seem to correlate with an increased progression to cancer in a murine model and human patients.…”
Section: Functional Relevance Of Dclk1 Expression In Malignancymentioning
confidence: 70%
“…Thus, O'Connell and colleagues were able to reconcile the apparent contradictory findings of widespread epigenetic silencing of the Dclk1C gene on one hand, and the clear functional importance of the transcript in a broad variety of cancers on the other. 41 Accordingly, Dclk1 expression has been observed in neuroendocrine tumors of the mammary gland and the rectum, 42,43 consistent with the known expression of Dclk1 in neuronal and enteroendocrine cells, but no specific role for Dclk1 in these tumors has been suggested so far. Finally, the relevance of Dclk1 expression in esophageal cancer is presently unclear, 44 but the cells seem to correlate with an increased progression to cancer in a murine model and human patients.…”
Section: Functional Relevance Of Dclk1 Expression In Malignancymentioning
confidence: 70%
“…We began examining possible use of an alternate promoter for expression of DCLK1 protein, to resolve the discrepancy between silencing of 5'promoter and presence of DCLK1 in hCRCs/ hCCCs. After extensive literature search and in silico analysis of hDCLK1 gene, we discovered that the previously suggested β promoter (11,45), was located in IntronV of the hDCLK1 gene, and had a canonical TATA box (9). The alternate β promoter was transcriptionally active in 80-90% of hCCCs and transformed (HEKmGAS) cells, but was inactive in non-transformed (HEK293) and normal colonic epithelial cells (9).…”
mentioning
confidence: 99%
“…After extensive literature search and in silico analysis of hDCLK1 gene, we discovered that the previously suggested β promoter (11,45), was located in IntronV of the hDCLK1 gene, and had a canonical TATA box (9). The alternate β promoter was transcriptionally active in 80-90% of hCCCs and transformed (HEKmGAS) cells, but was inactive in non-transformed (HEK293) and normal colonic epithelial cells (9). A transcript originating from the alternate β promoter was confirmed to match isoform 2 in the NCBI data base (NM_001195415.1) (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present study identified a positive association between DCLK1 expression and tumor intrahepatic metastasis, while no association was observed between DCLK1 expression and sex, grade, hepatic venous metastasis, portal venous metastasis, bile duct invasion or cirrhosis. Previous studies demonstrated that DCLK1 expression was associated with T stage and lymphatic vessel involvement in colorectal cancer (35). Although DCLK1 expression has been studied in HCC, there is little data on the expression and survival significance of DCLK1 in patients with HCC.…”
Section: Discussionmentioning
confidence: 97%